Viability of a rural electrification program in Peru - Hidalgo-Crespo, José; Bautista-Espinoza, Hugo; Oviedo, J. (EASI: Ingeniería y Ciencias Aplicadas en la Industria, 2022)
This research resumes the work carried out at the ACCIONA Micro Energy Foundation (FUNDAME) as part of the final internship and Master’s thesis for the 2014 European Joint Master’s in Management and Engineering of Environment and Energy Program (ME3). The internship took place in the Corporate Social Responsibility department of ACCIONA S.A. The internship consisted of improving the company´s business model to reach more isolated communities and effectuate preventive and corrective maintenance more sustainably. The step-by-step process used to implement this methodology in an economically sustainable manner using a fee-for-service model has been documented. In addition, the business model was evaluated to demonstrate its viability, impact, sustainability, and scalability during the systems’ lifetime; improvements were also analyzed. Due to the distance between ACCIONA Micro energy Peru (AMP) and the users, the costs of installation and maintenance of these systems can be significant. The new methodology, which states the implementation of Energy Supply and Service Centers (ESSC), has the potential to decrease project and operational costs and sustain itself over time.